Al-Sayyid, Abd al-Halim Mahmoud. “Creative Thinking: Its Concept, Necessity, and Means of its Development in Societies,” Year 11, Issue 41 (Summer 1426 AH/ 2005 CE), Pp. 47-88. - السيد عبد الحليم محمود (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2005)
Abd al-Halim al-Sayyid’s article begins with a discussion of the interest in human thinking in general, and in scientific thinking in particular, specifically in creative thinking, which is highly encouraged in Islam. His article tackles the psychometrics of creativity and the manifestations of creative activity, as well as the dimension of personal characteristics and its relationship with creativity. It also discusses the dimension of creative knowledge and methods of developing creative thinking, in addition to the social and psychological context of creativity in the family, and the Arab and Muslim societies’ need to develop creativity and examine its roots in Islamic culture. He concludes that there is a need for developing creative thinking in Islam, and the necessity of reformulating school and university curricula in order to enable scientific progress in developing creative thinking.